arfani IMPROVING ENGLISH PRONUNCIATION SKILL THROUGH THUMBELINA AND PINOCCHIO FAIRY TALES - Sri Arfani; Rini Martiwi; Oldea BrKaro Sekali (STIBA IEC JAKARTA, 2020)
As the objective of EFL teaching is to help students to communicate fluently in the target language, teachers should provide authentic models of language use for every level and age. To hit the target we should focus not only on linguistic, but also on literary and cultural elements. Since fairy tales offer these elements, they are highly beneficial to use in EFL teaching programs, especially for young learners. This objective of this research is to investigate the effectiveness of teaching English pronunciation through fairy tale media. This research was conducted at SMPS PGRI Pondokgede class 8-3. The writer has conducted field research for 1 month. Some data was taken through observation, process, and post-learning and teaching activities. This paper contains ways to improve students’ English pronunciation by providing Thumbelina and Pinocchio fairy tales. The result of this study indicated that: (1) teaching English pronunciation trough fairy tale is effective to increase students’ pronunciation (2) students become easier to understand the subject matter and increase their English vocabulary, and (3) students become more active and confident when reading texts or fairy tales by showing good pronunciation.